KEUNGGULAN BERSAING MEMEDIASI PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN - Palwaguna, I Komang Eddy Jaya; Yasa, Ni Nyoman Kerti (E-Jurnal Manajemen; Vol 10 No 12 (2021)DO - 10.24843/EJMUNUD.2021.v10.i12.p05, 2021)
Marketing performance is a measure of achievement obtained from the overall marketing process activities of a company or organization. The purpose of this study is to explain the effect of market orientation on marketing performance, effect of market orientation on competitive advantage, the effect of competitive advantage on marketing performance, and role of competitive advantage in mediating the effect of market orientation on marketing performance in UKM Batu Bata in Tulikup, Gianyar. The number of samples are 70 with non probality sampling method. Data collection through interviews and observations. The analysis technique used is Path Analysis. Based on the results, market orientation has a positive effect on the marketing performance, competitive advantage has a positive effect on the marketing performance and competitive advantage reduces the influence of market orientation on the marketing performance. Keywords: market orientation, competitive advantage, marketing performance